Teachers' Orientations toward Mathematics Curriculum Materials: Implications for Teacher Learning - Remillard, Janine T.; Bryans, Martha B. (Journal for Research in Mathematics Education, 2004)
This study was prompted by the current availability of newly designed mathematics curriculum materials for elementary teachers. Seeking to understand the role that reform-oriented curricula might play in supporting teacher learning, we studied the ways in which 8 teachers in the same school used one such curriculum, Investigations in Number, Data, and Space (TERC, 1998). Findings revealed that teachers had orientations toward using curriculum materials that influenced the way they used them regardless of whether they agree with the mathematical vision within the materials. As a result, different uses of the curriculum led to different opportunities for student and teacher learning. Inexperienced teachers were most likely to take a piloting stance toward the curriculum and engage all of its resources fully. Findings suggest that reform efforts might include assisting teachers in examining unfamiliar curriculum resources and developing new approaches to using these materials. (Contains 5 tables, 2 figures and 4 footnotes.)
Keywords: Class Activities; Classroom Observation Techniques; Curriculum Design; Educational Strategies; Educational change; Elementary School Mathematics; Faculty Development; Investigations; Longitudinal Studies; Teacher Attitudes; Teaching Experience; mathematics curriculum